Evaluation of Feed Nutritional Content on The Laying Hens Productivity In East Lombok Regency - Vebera Maslami; Dwi Kusuma Purnamasari; K.G.Wiryawan; Erwan; Syamsuhaidi; Sumiati; Azhary Noersidiq; Fahrullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The performance of laying hens is affected by feed quality and can be seen from feed consumption, egg weight and hen day production (HDP). The aim of this study was to determine the quality of feed on the performance of laying hens. Sampling was carried out via interview on farmers in East Lombok representing each sub-district with a minimum population of 500 laying hens. Sampling of feed ingredients and 20 eggs was carried out on each farm for analysis in the laboratory. The descriptive analysis was performed on acquired data. The results showed that farmers in East Lombok used different percentages of corn, concentrate and mineral feed ingredients. The nutritional content of feed given consist of crude protein (14,17-16,90%), crude fat (3,17-3,36%), crude fiber (6,13-7,06%), calcium (1, 03-1,29), phosphorus (0,26-1,33%) and metabolic energy (2751,96-2925,79 Kcal/kg). The conclusion is some farmers in East Lombok Regency provide feed that does not suitable to the nutritional needs required by laying hens, namely the content of crude protein, calcium and phosphorus according to SNI standards which has an impact on reducing egg weight and HDP.